2022
DOI: 10.3390/biomedicines10112693
|View full text |Cite
|
Sign up to set email alerts
|

Sirtuin 7 Inhibitor Attenuates Colonic Mucosal Immune Activation in Mice—Potential Therapeutic Target in Inflammatory Bowel Disease

Abstract: Accumulating evidence has shown that sirtuin 7 (SIRT7), a mediator of various cellular activities, plays an important role in the pathogenesis of various immune-mediated inflammatory disorders. However, information remains limited regarding the role of SIRT7 in intestinal inflammation. We used a murine colitis model to investigate the role of SIRT7 in intestinal immunity and whether SIRT7 inhibitors could attenuate the intestinal inflammatory response. Mice were divided into three groups: control, colitis-indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
2
0
1
Order By: Relevance
“…Given that SIRT7 is involved in various immune-mediated inflammatory responses (including the NF-kB inflammatory pathway), SIRT7 may, therefore, be closely associated with intestinal immune-mediated inflammatory responses, such as inflammatory bowel disease (IBD). Kim et al showed that SIRT7 attenuated colonic mucosal inflammation in mice (42). Overall, there are many studies on the mechanisms of SIRTs family involvement in inflammation, especially involving NF-kB, TNF-a, NLRP3, and MAPK-related pathways.…”
Section: Relationship Between Sirts and Immune Inflammationmentioning
confidence: 99%
“…Given that SIRT7 is involved in various immune-mediated inflammatory responses (including the NF-kB inflammatory pathway), SIRT7 may, therefore, be closely associated with intestinal immune-mediated inflammatory responses, such as inflammatory bowel disease (IBD). Kim et al showed that SIRT7 attenuated colonic mucosal inflammation in mice (42). Overall, there are many studies on the mechanisms of SIRTs family involvement in inflammation, especially involving NF-kB, TNF-a, NLRP3, and MAPK-related pathways.…”
Section: Relationship Between Sirts and Immune Inflammationmentioning
confidence: 99%
“…Присутствие LPS из Bacteroides fragilis в сыворотке крови вносит вклад в воспаление при ВЗК [da Silva et al, 2023]. Недостатками препаратов первой линии терапии при ВЗК, включая производные 5-аминосалициловой кислоты, глюкокортикостероиды, иммуносупрессоры, генно-инженерные биологические препараты, являются побочные эффекты, в том числе системная иммуносупрессия, индивидуальная непереносимость, рефрактерность более чем у 30% пациентов [Kim et al, 2022]. В связи с этим, востребованной становится разработка новых, обоснованных с патогенетических позиций и безопасных лекарственных средств преимущественно локального действия с активными веществами эндогенного или растительного происхождения.…”
Section: Introductionunclassified
“…Kim and colleagues evaluated the effectiveness of inhibiting Sirtuin 7 (SIRT7) in a colitis mouse model. The study revealed that inflammatory cytokines and mucosal inflammation extent were suppressed in colitis-induced mice treated with the SIRT7 inhibitor, indicating SIRT7 as a potential novel target for IBD treatment [ 7 ]. Furthermore, high-quality clinical trials were published in the second edition of this Special Issue.…”
mentioning
confidence: 99%